ANALISIS REPRESENTASI PEREMPUAN DALAM PUISI “BERSATULAH PELACUR – PELACUR KOTA JAKARTA” KARYA W.S. RENDRA (KAJIAN FEMINISME MARXIS) - Manoppo, Kristopan; Bagtayan, Zilfa A. (Jurnal Bahasa, Sastra, dan Budaya, 2025)
This article aims to analyze the representation of women in the poem "Bersatulah Pelacur-Pelaprostitu Kota Jakarta" by W.S. Rendra using a Marxist feminism approach. In this analysis, the author examines how the poem depicts the position of women, mainly prostitutes, in the social and economic context of Jakarta at that time. Using Marxist feminist theory, which emphasizes social class inequality and the exploitation of women in the capitalist system, Rendra's poem is interpreted as a critique of patriarchal domination as well as social structures that oppress women, especially those trapped in the sex industry. The results of the analysis show that Rendra seeks to arouse readers' awareness of women's struggle to gain recognition and freedom from oppression, as well as voice concern about the social reality that marginalizes women. In this context, poetry becomes a medium to depict the complex realities of the relationship between capitalism, patriarchy, and women's suffering.